Analisis Pengaruh Masa Kerja, Lingkungan Kerja dan Employee Enggagement terhadap Kinerja Karyawan Non Medis RS Aura Syifa Kediri - Fitriawan, Andika Happy; Fajariah, Nuraidya; Hidayati, Nur (Jurnal Bisnis Islam dan Kewirausahaan, 2023)
This research aims to determine the influence of work period, work environment and employee engagement on the performance of non-medical employees at Aura Syifa Hospital Kediri. The method used in this research is quantitative descriptive. The population and sample used in this research are non-medical employees working at Aura Syifa Hospital Kediri who are still actively working until 2022, totaling 55 people. The sampling method used in this research used saturated samples. Data processing in this research uses validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination (R2), t test and F test. The results of this research are that length of service has a partial effect on employee performance with a significant value of 0.013 < 0.05. The work environment has a partial effect on employee performance with a value of 0.016 < 0.05. Employee engagement partially influences employee performance with a significant value of 0.030 <0.05. Years of work, work environment and employee engagement simultaneously influence employee performance with a significant value of 0.000 < 0.05